Ionic liquids as catalysts of lignocellulosic biomass processing - Carvalho, Ana Vanessa Antunes (2014)
The present work is devoted to study the pre-treatment of lignocellulosic biomass, especially wheat straw, by the application of the acidic ionic liquid (IL) such as 1-butyl-3-methylimidazolium hydrogen sulphate. The ability of this IL to hydrolysis and conversion of biomass was scrutinised. The pre-treatment with hydrogen sulphate-based IL allowed to obtain a liquor rich in hemicellulosic sugars, furans and organic acids, and a solid fraction mainly constituted by cellulose and lignin. Quantitative and qualitative analyses of the produced liquors were made by capillary electrophoresis and high-performance liquid chromatography. Pre-treatment conditions were set to produce xylose or furfural. Specific range of temperatures from 70 to 175 °C and residence times from 20.0 to 163.3 min were studied by fixing parameters such as biomass/IL ratio (10 % (w/w)) and water content (1.25 % (w/w)) in the pre-treatment process. Statistical modelling was applied to maximise the xylose and furfural concentrations. For the purpose of reaction condition comparison the severity factor for studied ionic liquid was proposed and applied in this work. Optimum conditions for xylose production were identified to be at 125 °C and 82.1 min, at which 16.7 % (w/w) xylose yield was attained. Furfural was preferably formed at higher pre-treatment temperatures and longer reaction time (161 °C and 104.5 min) reaching 30.7 % (w/w) maximum yield. The influence of water content on the optimum xylose formation was also studied. Pre-treatments with 5 and 10 % (w/w) water content were performed and an increase of 100 % and 140 % of xylose yield was observed, respectively, while the conversion into furfural maintained unchanged.